The Effect of SNI 6729 : 2016 on Organic Vegetables Purchase Intention and Purchase Behavior (Case Study : PT Rumah Roti Indonesia) - Nugroho, Imanuella Indah; Fahma, Fakhrina; Damayanti, Retno Wulan (Jurnal Teknik Industri: Jurnal Keilmuan dan Aplikasi Teknik Industri, 2022)
At a time when the people's increasing demand for organic vegetables can be an opportunity for PT Rumah Roti Indonesia to expand its market beyond the scope of PT Rumah Roti Indonesia. Organic certification is one way to expand the market. The aim of this study is analyze the effect of SNI 6729: 2016 certification on purchase intention and purchase behavior of organic vegetables in Indonesia so that PT Rumah Roti can take the right decision. To see the effect of SNI 6729 : 2016, this study uses the Theory of Planned Behavior model. Data processing was used in the PLS-SEM method. The results of this study prove that the variables perceived behavioral control, subjective norms, and perceived quality have a significant effect on purchase intention in organic vegetables and awareness has a significant effect on moderating the relationship between purchase intention and purchase behavior. In addition, it was found that purchase intention has a significant effect on purchase behavior. These results indicate that there is an influence of SNI 6729 : 2016 on purchase intention and purchase behavior of organic vegetables.